1987
DOI: 10.1099/0022-1317-68-9-2281
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Immune-stimulating Complexes Containing Hepatitis B Virus Surface Antigen

Abstract: SUMMARYImmune-stimulating complexes (iscoms) have been prepared containing the major S gene products (HBsAg) of the hepatitis B virus genome. Immunization of BALB/c mice with a single dose of hepatitis B iscoms in saline resulted in a high titre antibody response to HBsAg. In contrast, the original HBsAg preparation required an adjuvant to produce equivalent amounts of antibody. Analysis of sera from mice immunized with hepatitis B iscoms revealed antibodies directed against the major a determinants of HBsAg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…Alum was required as an ad-CHARACTERISTICS AND USE OF NE W-GENERA TION ADJUVANTS 535 juvant to enhance immunogenicity of these particles. Immunization of mice with iscoms containing HBsAg derived from yeast generated high levels of HBVspecific antibodies (Howard et al, 1987).…”
Section: Hepatitis B Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Alum was required as an ad-CHARACTERISTICS AND USE OF NE W-GENERA TION ADJUVANTS 535 juvant to enhance immunogenicity of these particles. Immunization of mice with iscoms containing HBsAg derived from yeast generated high levels of HBVspecific antibodies (Howard et al, 1987).…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Quil A is a necessary constituent of the iscom structure. The size and morAntigen nature Name Mowatt et al, 1991a/b Lovgren et al, 1987Erturk et al, 1989Trudel et al, 1987, 1988Wahren et al, 1987Tsuda et al, 1991Morgan et al, 1988Howard et al, 1987Trudel et al, 1988Carlson et al, 1991De Vries et al, 1988aDe Vries et al, 1988bVisser et al, 1989Trudel et al, 1989Trudel et al, 1992Fedaku et al, 1992Jones et al, 1988Merza et al, 1991Osterhaus et al, 1992Takehashi et al, 1990Pyle et al, 1989Nagy et al, 1990Winter et al, 1988…”
mentioning
confidence: 99%
“…They combine the characteristics of multimeric presentation of antigen with an inbuilt adjuvant Sundquist et al, 1988) and vaccines utilizing these properties are now being developed, including a hepatitis B virus vaccine (Howard et al, 1987). Protective immunity has been obtained against feline leukaemia virus (FeLV) in cats following vaccination with iscoms carrying the gp70/85 component of FeLV (Osterhaus et al, 1985).…”
Section: Short Communicationmentioning
confidence: 99%
“…A novel structure for the antigenic presentation of membrane proteins from enveloped viruses has been shown to be highly effective in inducing both humoral and cell-mediated immune responses: the immune-stimulating complex (iscom) (Morein et al, 1984;Morein & Simons, 1985;Osterhaus et al, 1985;Wahren et al, 1987;Howard et al, 1987). It was demonstrated that MV membrane proteins presented in iscom form elicited not only VN and HI antibodies, but also (non-HI) HLI antibodies in rats (Morein et al, 1984).…”
Section: Introductionmentioning
confidence: 99%